Preliminary study of sound touch elastography in diffuse thyroid disease in children - Li, Lin; Zhang, Aimei; Chen, Dan; Taragin, Benjamin H.; Luo, Xiaoyong (Frontiers in Pediatrics, 2022)
Objective: The purpose of this study was to determine the use of sound touch elastography (STE) in conjunction with conventional ultrasound in the differential diagnosis of diffuse thyroid disease (DTD) and normal thyroid in children. Methods: Studies performed on 62 children with DTD and 30 normal volunteers were reviewed. Standard grey scale ultrasound and STE of the examinees, and the serum test results of children with DTD were collected, analyzed and compared. Results: The STE-Mean values in the Graves' disease (GD) group, Hashimoto's thyroiditis (HT) group, and normal control group, respectively, were 19.35±5.00 kPa, 19.43±6.06 kPa, and 11.24±1.99 kPa. With an area under the ROC curve (AUC) of 0.945, STE-Mean values differentiated DTD from normal children. The peak systolic velocity(PSV) of the superior thyroid artery separated DTD from normal children and AUC from children with GD and HT, respectively, and was 0.992 and 0.864. The PSV of superior thyroid artery revealed a somewhat favorable connection with FT3 and FT4. Conclusion: The STE results revealed that thyroid stiffness was higher in children with DTD than in normal children, but the differential diagnosis of GD and HT lacked specificity, and the superior thyroid artery flow velocity might be a good supplement to both.